The Influence Of Social Media And Influencer Marketing On Food & Drink Buying Interest At Moon Beach Club, Lhoknga, Aceh Besar - Fuad, Ammar; Murni, Mirza; Farizi, Hafidz (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The researcher intends to test the influence of social media and influencer marketing on the interest in buying food & drinks at Moon Beach Club, Lhoknga, Aceh Besar. In theory, both variables influence buying interest. However, the researcher found phenomena and inconsistencies between the results of previous studies so that the researcher intends to re-test the influence of the two variables. The purpose of this study is to test and analyze the influence of social media and influencer marketing on the interest in buying food & drinks at Moon Beach Club partially and simultaneously. The research method used is a quantitative method with an associative type. Meanwhile, the data for this study are primary data obtained through a questionnaire with a total of 96 respondents. The results of the study indicate that social media and influencer marketing influence the interest in buying food & drinks at Moon Beach Club, Lhoknga, Aceh Besar.